2011
DOI: 10.3791/3573
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Somatic Hypermutation in Ramos B Cells after Overexpression or Knockdown of Specific Genes

Abstract: B cells start their life with low affinity antibodies generated by V(D)J recombination. However, upon detecting a pathogen, the variable (V) region of an immunoglobulin (Ig) gene is mutated approximately 100,000-fold more than the rest of the genome through somatic hypermutation (SHM), resulting in high affinity antibodies 1,2 . In addition, class switch recombination (CSR) produces antibodies with different effector functions depending on the kind of immune response that is needed for a particular pathogen. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…We report the establishment of a cell line that can be used to address in vitro the mechanism of A/T mutations during the process of somatic hypermutation of Ig genes. The Ramos Burkitt cell line has been widely used to study the mechanism of SHM in vitro (19,37,38). Ramos cells exhibit most of the features of SHM in vivo except that the spectrum of mutations displays a deficiency in A/T mutations.…”
Section: Discussionmentioning
confidence: 99%
“…We report the establishment of a cell line that can be used to address in vitro the mechanism of A/T mutations during the process of somatic hypermutation of Ig genes. The Ramos Burkitt cell line has been widely used to study the mechanism of SHM in vitro (19,37,38). Ramos cells exhibit most of the features of SHM in vivo except that the spectrum of mutations displays a deficiency in A/T mutations.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the functional effects on SHM, we subjected the parental A23 cell line and the KO subclones to an IgM loss assay in which loss of IgM expression, detected by flow cytometry, serves a read‐out for levels of SHM at the Ig loci . We first confirmed that IgM loss was AID‐dependent by assaying AID KO cells (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The transfection media was replaced with 2 mL of UltraCULTURE media (Lonza 12–725F) supplemented with 1× Glutamax (Gibco 35050061) and 0.1 mg/mL Normocin 4 h later. Forty‐eight hours after transfection the viral supernatant was collected and Ramos cells were transduced as reported previously .…”
Section: Methodsmentioning
confidence: 99%
“…Ramos cells were plated at a density of 2.5 × 10 5 cells/ml and infected with the GPX4 lentivirus or empty construct by centrifugation at 3000× rpm for 90 min at room temperature (25 °C), as described previously ( 54 ). The cells were then cultured for 48 h before antibiotic selection was initiated.…”
Section: Methodsmentioning
confidence: 99%